Peri urban floriculture: A comparative study from NCR on production, value addition, marketing and constraints - GILLS, RESHMA; SHARMA, J P; BURMAN, R R; SHARMA, R R; KAR, AMIT (The Indian Journal of Agricultural Sciences, 2017)
Floriculture sector in India is gaining momentum in the contribution of economic well being of the small and marginal farmers due to its vast entrepreneurial potential. Even if the flower industry is flourishing, farm gate price to the farmers is very low owing to post harvest losses and intervention of middle men in marketing. Post harvest operation and value addition in the flower is an important option to decrease the losses and increase the net returns to the farmers. An attempt has been made here to identify marketing channels, marketing efficiency and price spread of the identified marketing channels among flower producers and processors in Faridabad district of Haryana state. Study revealed a statistically significant higher net income to the processors (t = 44.030, p < 0.05) even if cost of production for the value added flower is high (t = 4.154, p < 0.05). Producers share in consumers' price showed huge variation among different identified channels. Increasing demand of flower products in urban areas motivated the processors to do the value addition (Mean Rank of Friedman's Test is 9.75). Kruskal-Wallis one-way ANOVA (c2 =30.424, df = 3, p < 0.05) employed for the identification of the constraints revealed that market related constraints were severe one. Present study highlighted the importance of market intelligence and timely accessibility of sufficient decision supporting data to manage and market the flower products.